2008
DOI: 10.1007/s11251-008-9069-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the deep-level reasoning questions effect during vicarious learning among eighth to eleventh graders in the domains of computer literacy and Newtonian physics

Abstract: This paper tested the deep-level reasoning questions effect in the domains of computer literacy between eighth and tenth graders and Newtonian physics for ninth and eleventh graders. This effect claims that learning is facilitated when the materials are organized around questions that invite deep-reasoning. The literature indicates that vicarious learners in college student populations show greater pretest to posttest learning gains when presented with deep-level reasoning questions before each content sentenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
2
24
1
Order By: Relevance
“…Based on correlational evidence from the fine-grained analysis of gist explanation dialogues, the questions, "what is breast cancer," and "how does breast cancer grow and spread" were associated with smaller gains in outcome measures. These results seem to corroborate other findings on deep-level reasoning questions (Craig et al, 2012; Gholson et al, 2009). The effectiveness of asking participants to provide explanations in their own words is worthy of future experimental work.…”
Section: 1 Discussionsupporting
confidence: 91%
“…Based on correlational evidence from the fine-grained analysis of gist explanation dialogues, the questions, "what is breast cancer," and "how does breast cancer grow and spread" were associated with smaller gains in outcome measures. These results seem to corroborate other findings on deep-level reasoning questions (Craig et al, 2012; Gholson et al, 2009). The effectiveness of asking participants to provide explanations in their own words is worthy of future experimental work.…”
Section: 1 Discussionsupporting
confidence: 91%
“…Students' liking of an AutoTutor agent also had no correlation with learning as reported by Moreno et al (2002), whereas Jackson and Graesser (2007) reported a negative relationship between conditions that promote liking versus deep learning. Studies on vicarious learning have identified some conditions when the human does not even need to be directly interacting with the tutor, but can learn fairly well by watching a simulated student learn (Gholson et al 2009;Chi et al 2008). In total, this suggests that pedagogical agents do not need to be navigators or buddies to the learner, nor even liked by the learner.…”
Section: Discussion: Key Findings From Autotutormentioning
confidence: 99%
“…This vicarious learning research followed up on a study that reported that adaptive conversational interaction was only slightly more effective than presenting succinct, targeted script content that directly answered the main question (Graesser et al 2004b). Research on iDRIVE revealed that vicarious learning with deep questions performed comparably to AutoTutor on physics (Gholson et al 2009). Vicarious dialogs where the peer student modeled asking deep questions also increased question asking by students, which is a metacognitive strategy that improves learning (Craig et al 2006;Rosenshine et al 1996).…”
Section: Vicarious Agent Demonstrationsmentioning
confidence: 99%
“…SKO and AutoTutor draw heavily on tutoring research about self-explanation and elaboration and has benefitted from continuous research and development for over twenty years. AutoTutor has been shown to be successful in multiple academic domains, such as physics and computer science (Craig, Sullins, Witherspoon, & Gholson, 2006;Gholson et al, 2009;Jackson, Ventura, Chewle, Graesser, & the Tutoring Research Group, 2004). AutoTutor's successful natural-language interaction style of expectation and misconception tailored dialogue (Graesser, Chipman, et al, 2005;Graesser, Person, & Magliano, 1995) uses scripts that include a set of expectations as well as misconceptions learners are likely to entertain.…”
Section: Tutoring and Self-explanationmentioning
confidence: 99%